PENGARUH STAD BERBASIS PERCOBAAN TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA KELAS V SD - Bela Wati; Hery Kresnadi; Siti Halidjah (Universitas Tanjungpura, 2019)
AbstractThis study aimd to analyze the effect of using the experimental-based student teams achievement divisions model on student learning outcomes 5th grade natural science subject of elementary 38 school in northern Pontianak. The method used was the experimental method, the form of research used was quasi experimental design with the design of nonequivalent control group design. The population and sample in this study were all 5th grade students of Elementary 38 School in Northern Pontianak. The data collection tool was a multiple choice test with 45 questions. Based on data analysis, the average post-test results of the experimental class were 77,50 while the average post-test results of the control class 69,22. The results of the t test obtained tcount of 3,899 and ttable α = 5% (with dk = 20 + 23 - 2 = 41)is 2,020 ,which means tcount (3,899)> ttable (2,020), then Ha is accepted. It was concluded that there is a effect of using the experimental-based student teams achievement divisions model on student learning outcomes natural science subject of elementary school. From the results of ES calculations, obtained ES for 0,98 (high criteria). This means using the experimental-based student teams achievement divisions model give a good effect on student learning outcomes in grade V natural science subject of elementary 38 school in northern Pontianak. Keywords: Experimental-Based Student Teams Achievement Divisions, Learning Outcomes, Natural Science